A Mononuclear and a Mixed-Valence Chain Polymer Arising from Copper(II) Halide Chemistry and the Use of 2, 2'-Pyridil. (15th July 2007) - Milios, Constantinos J.; Raptopoulou, Catherine P.; Terzis, Aris; Perlepes, Spyros P.; Papaefstathiou, Giannis S.
Abstract : Reactions of 2, 2 ' -pyridil (pyCOCOpy) with CuCl 2 ⋅ 2 H 2 O and CuBr 2 in EtOH yielded the mononuclear complex [ Cu ( pyCOOEt ) 2 Cl 2 ] ⋅ H 2 O (1 ) and the one-dimensional, mixed-valence complex [ Cu 2 I Cu II ( pyCOOEt ) 2 Br 4 ] n (2 ), respectively. Both complexes crystallize in the triclinic space group P 1 ¯ . The lattice constants are a = 8.382 (2), b = 9.778 (2), c = 7.814 (2), α = 101.17 (1), β = 114.55 (1), γ = 94.14 ( 1 ) ∘ for 1 and a = 8.738 (1), b = 9.375 (2), c = 7.966 (1), α = 79.09 (1), β = 64.25 (1), γ = 81.78 ( 1 ) ∘ for 2 . 2, 2 ' -pyridil undergoes a metal-assisted alcoholysis and oxidation leading to decomposition and yielding the ethyl picolinate (pyCOOEt) ligand. The autoredox process associated with the reduction of copper(II) to copper(I) in the case of complex 2 is discussed in terms of the increased redox activity of the copper(II) bromide system relative to the copper(II) chloride system.